Graded Distribution of Solute Particles in Centrifugal Casting - Mohapatra, Shubhashree; Hrushikesh Sarangi, Dr.; U.K.Mohanty, Dr. (International Journal of Engineering and Technology, 2018)
The paper analyzed the processing factors responsible for gradation of second phase, rejected solute particles in centrifugal casting that would lead to the production of functionally graded materials (FGMs). The experiment conducted under laboratory simulated conditions involved the solidification of molten wax as the matrix and wood and sand particles as reinforced materials, in a rotating mould. The use of the prototype to establish the influence of the processing factors could be accomplished at a considerably low cost and was decisive in fixing the effect of these factors like the rotational speed of the mould and mould dimension in the real life metal casting paving a way for tailoring the FGMs keeping an eye to its specific end use.Â Â